ECONOMIC POLICY OF KURBANJON DADKHOX - Qodirova Mavluda Mirzaraximovna (TARIXIY TADQIQOTLAR, 2026)
The article decsribes the economic policy of Qurbanjon Dodkhoh. The work studies his economic strategies in state administration, tax system, land and water policy, reforms implemented through crafts and trade relations. Also, aspects such as economic justice, financial stability, protection of the domestic market and the standard of living of the population are shown with extended scientific explanations and prepared on the basis of historical sources, literary works and modern scientific research.